2016
DOI: 10.1080/03736687.2015.1123344
|View full text |Cite
|
Sign up to set email alerts
|

New national and regional bryophyte records, 46

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 84 publications
0
7
0
1
Order By: Relevance
“…The species richness of mosses in the study area is very high; 40% of the total of 766 species and infra-specific taxa reported from Borneo and 47% of the total of 651 species and infra-specific taxa reported from Sabah (Andi and Suleiman 2005, Suleiman et al 2006, 2009, 2011a, 2011b, 2017, Suleiman and Akiyama 2007, Higuchi et al 2008, Akiyama 2010, Ho et al 2010, Ellis et al 2010, 2015, 2016a, 2016b, Andi et al 2015, Chua and Suleiman 2015, Mohamed et al 2010, Suleiman and Rimi 2016). …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The species richness of mosses in the study area is very high; 40% of the total of 766 species and infra-specific taxa reported from Borneo and 47% of the total of 651 species and infra-specific taxa reported from Sabah (Andi and Suleiman 2005, Suleiman et al 2006, 2009, 2011a, 2011b, 2017, Suleiman and Akiyama 2007, Higuchi et al 2008, Akiyama 2010, Ho et al 2010, Ellis et al 2010, 2015, 2016a, 2016b, Andi et al 2015, Chua and Suleiman 2015, Mohamed et al 2010, Suleiman and Rimi 2016). …”
Section: Resultsmentioning
confidence: 89%
“…Five of these species, namely Claopodium prionophyllum , Entodon plicatus , Erythrodontium squarrosum, Mesonodon flavescens and Oxyrrhynchium vagans , have only been collected once in Borneo (Dixon 1916, Iwatsuki and Noguchi 1975, Akiyama et al 2001). Elmeriobryum philippinense was collected during the study and reported as new to Borneo by Ellis et al (2016a). In addition, three species endemic to Borneo were also found in this park: Benitotania elimbata , Ectropothecium ptychofolium and Acroporium ramicola (Appendix 1).…”
Section: Resultsmentioning
confidence: 98%
“…Pohlia cruda has a pantemperate distribution in the southern hemisphere and its range covers southern South America, Lesotho in South Africa and SE Australia, Tasmania and New Zealand with some offshore islands (Ochyra et al, 2008a). Pohlia cruda is a bipolar species with some intermediate stations in the northern Andes and recently it was also discovered in East Africa (Blockeel et al, 2007;Ellis et al, 2016a). This is the first recently confirmed record of Pseudocalliergon lycopodioides in the Western Carpathians.…”
mentioning
confidence: 52%
“…Among the four archipelagoes or island groups in this province, the Prince Edward Islands have the best studied moss flora, consisting of about 100 species [57][58][59][60][61][62][63][64]. Likewise, the highly isolated and heavily glaciated Heard Island has a fairly well studied moss flora [65,66] consisting of about 60 species. In contrast, the moss flora of Îles Crozet was least known until the late 1970s and about 40 species have so far been recorded from Île de la Possession and Île de l'Est, the two largest islands of this archipelago [67,68].…”
Section: Studies On the Bryophyte Flora Of The Subantarcticmentioning
confidence: 99%